THE EFFECT OF WORKING CAPITAL, PRODUCTION COSTS, OPERATIONAL COSTS, DISTRIBUTION, AND SALES COSTS ON NET PROFIT: In Pharmaceutical Subsector Companies Listed on the Indonesia Stock Exchange in 2014-2021 - Hafizah, Nurul; Alamsyah, Muhammad Iqbal (Journal of Accounting Inaba, 2023)
The research method used in this study is a descriptive and verification research method. The data used is secondary data. Data collection uses library research and documentation obtained from the official website of the Indonesia Stock Exchange. Sampling used a purposive sampling method and obtained data from 2014 – 2021 The pharmaceutical industry sub-sector is listed on the Indonesia Stock Exchange. The data analysis technique used in this study is the classical assumption test, multiple regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The results of the study show that working capital has a significant effect on net income. This statement is proven by the results of the t test which produces t count > t table of 4.393 > 2.030 with a significance level of 0.00 <0.05. Production Costs have no effect on Net Income. This statement is proven by the results of the t test which produces t count < t table of 1.055 < 2.030 with a significance level of 0.299 > 0.05.